2008
DOI: 10.1007/s00264-007-0504-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of external fixation, locking and non-locking palmar plating for unstable distal radius fractures in the elderly

Abstract: This study compares the effectiveness of locking and non-locking palmar plating and external fixation for unstable distal radius fractures in the elderly. In a retrospective match-paired study, 45 patients aged 50 to 70 years who underwent surgery for C1/C2 distal radius fractures were evaluated. The surgical procedures were external fixation or plating with locking or non-locking palmar plates. Radiological and functional outcomes were assessed. Outcomes according to Gartland and Werley, Martini and the Disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 25 publications
(41 reference statements)
3
55
2
1
Order By: Relevance
“…Previous literature has estimated a 10-point difference in the DASH score to be clinically meaningful [13,18]. Recent studies administering the DASH to patients with distal radius fractures have shown that a standard deviation of DASH scores ranging from 5 to 10 points allowed for an accurate power analysis [6,34,37,42]. Using these parameters in the literature-a mean difference of 10 points, and a standard deviation of 10-we determined with an alpha of 0.05 a minimum of 17 patients per group were required to detect a significant difference with a two-tailed independent samples t test between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has estimated a 10-point difference in the DASH score to be clinically meaningful [13,18]. Recent studies administering the DASH to patients with distal radius fractures have shown that a standard deviation of DASH scores ranging from 5 to 10 points allowed for an accurate power analysis [6,34,37,42]. Using these parameters in the literature-a mean difference of 10 points, and a standard deviation of 10-we determined with an alpha of 0.05 a minimum of 17 patients per group were required to detect a significant difference with a two-tailed independent samples t test between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Limiting soft tissue irritation and providing earlier wrist motion, this technique may be an alternative to known methods for unstable fractures. Several devices were introduced with promising outcomes in treatment of extra-articular and simple intra-articular distal radius fractures [7][8][9][10]. However, to our knowledge, there has been no comparative clinical study reporting outcomes regarding the use of Sonoma Wrx (Sonoma Orthopedic Products, Santa Rosa, CA) in treatment of extra-articular and simple intraarticular distal radius fractures.…”
Section: Introductionmentioning
confidence: 96%
“…The objective measures are consistently better with internal fixation, but the outcome measures are very similar between operative and nonoperative treatment groups. 276,[282][283][284] A more specific outcome measure for fracture treatment is needed and is a potential for further study. The DASH outcome measure may not be appropriate for distal radius fractures in the older patient population.…”
Section: Surgical Treatmentmentioning
confidence: 99%